Prediction of the competitiveness dynamics of pharmacy chains - Posylkina, Olga; Mala, Zhanna; Nessonova, Marina (ScienceRise: Pharmaceutical Science, 2017)
In market economy, one of the main tasks of any enterprise (organization) is to defeat rival competitors. It should not be single or random victory, but it should be natural result of effective management of this process. Aim of the present study was development of the methodical approaches for the pharmacy chains competitiveness dynamics modelling under volatile market situation conditions. Methods. Multivariate correspondence analysis method was used for research. Results. 53 indexes influencing on the resulting indicator level were analyzed initially for prediction of the pharmacy chains competitiveness dynamic. Using a multiple correspondence analysis, a mathematical model was developed; the model allows predicting the pharmacy chains competitiveness dynamics on the basis of the "competitiveness index" calculation - a numeric index taking positive values in case of increasing competitiveness and negative ones - in case of the absence of its positive dynamics. Conclusion. Methodical approaches to the pharmacy chains competitiveness prediction that allow making management decisions aimed at negative external influences resisting and leadership achieving according to the organization's strategic goals were offered